Clinical and MRI patterns of pericallosal artery infarctions: the significance of supplementary motor area lesions - Alonso, Angelika; Gass, Achim; Roßmanith, Christina; Kern, Rolf; Griebe, Martin; Binder, Johannes; Hennerici, Michael G.; Szabo, Kristina (Journal of neurology, 2011)
Cerebral infarctions in the anterior cerebral artery (ACA) territory account for only up to 3-5% of strokes. Subject to the affected ACA branches, different clinical patterns can be defined. We report a case series of patients with isolated infarctions of the pericallosal (PC) artery territory. We analyzed 36 consecutive patients presenting over a 10-year period with isolated PC artery territory infarctions (15 left-sided, 19 right-sided, 2 bilateral) regarding clinical symptoms as well as MRI findings. Analysis of DWI lesion pattern showed complete PC artery infarctions in three patients. The majority of patients had partial infarctions predominantly involving either the superior frontal gyrus (n = 12), the corpus callosum (n = 1) or both (n = 20). Hemodynamic lesion patterns were found in 13 patients, while multiple cortical emboli occurred in six. Distal pathology of the ACA (n = 13) was the most frequent MRA finding. Core symptom was contralateral hemiparesis with lower limb predominance (n = 29), partly associated with early-onset spasticity. Interestingly, motor evoked potential recording was abnormal in only five patients. Further characteristic symptoms were psychomotor slowing (n = 9), often with speech disturbances such as decreased verbal fluency, and confusional state (n = 4). Visual or motor hemineglect (n = 5) as well as apraxia (n = 5) was confined to a few patients only. Pericallosal artery infarctions are a rare localization of stroke, mostly occurring as partial infarctions due to distal ACA pathology. Clinically, they are mainly characterized by hemiparesis predominately in the lower limb caused by involvement of supplementary motor cortex areas without affection of the corticospinal tract.